2018
DOI: 10.1039/c7ra12512g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage in Li, Na and Ca decorated and defective borophene: a first principles study

Abstract: Recently synthesized two-dimensional (2D) borophene possesses unique structural, mechanical, electrical and optical properties. Herein, we present a comprehensive study of H 2 storage in alkali metal decorated and defect containing 2D borophene using density functional theory calculations. While the adsorption of H 2 over pristine borophene was found to be weak with a binding energy of À0.045 eV per H 2 , metal decoration and point defects enhanced the adsorption strength significantly. Interestingly, the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Li, Na, and Ca‐doped defective borophene sheets (2‐ Pmmn ) were used by Halder et al. [ 115 ] to study their hydrogen storage capacity using DFT calculations. Figure 15f represents the relaxed configurations of Li, Na, and Ca decorated borophene sheets, where red, blue, and purple balls denote Li, Na, and K atoms, respectively.…”
Section: Environmental and Energy Applicationsmentioning
confidence: 99%
“…Li, Na, and Ca‐doped defective borophene sheets (2‐ Pmmn ) were used by Halder et al. [ 115 ] to study their hydrogen storage capacity using DFT calculations. Figure 15f represents the relaxed configurations of Li, Na, and Ca decorated borophene sheets, where red, blue, and purple balls denote Li, Na, and K atoms, respectively.…”
Section: Environmental and Energy Applicationsmentioning
confidence: 99%
“…Haldar et al also reported as imilars tudy on the H 2 storagec apacities of Li-, Na-, andC a-incorporated and defective borophene systems. [68] DFTcalculations show that alkali and alkaline earth metal decoration enhances the H 2 storage capacityo fb orophene-based systems. Borophenes hows excellent mechanical properties, with aY oung's modulus of 398 GPa nm, and exhibits Dirac transport properties and superconductivity,a sw ell as ah ydrogen gravimetric density of 7.5 wt %.…”
Section: Hydrogen-storage Applications Of Borophene and Boron Fullerenementioning
confidence: 99%
“…Haldar et al. also reported a similar study on the H 2 storage capacities of Li‐, Na‐, and Ca‐incorporated and defective borophene systems . DFT calculations show that alkali and alkaline earth metal decoration enhances the H 2 storage capacity of borophene‐based systems.…”
Section: Hydrogen‐storage Applications Of Borophene and Boron Fullerenementioning
confidence: 99%
“… 41 This approach is commonly used in other studies of H 2 storage on 2D metal-decorated substrates. 13 , 15 , 18 , 27 , 42 An inter-layer separation of more than 30 Å is used to prohibit inter-layer interactions. 19 Nevertheless, a smaller inter-layer spacing may also be applicable.…”
Section: Computational Detailsmentioning
confidence: 99%
“… 13 , 15 19 Examples of such adjustments include external charge modulation, 16 , 17 and introduction of decorating atoms (mainly metals such as Li), which enhance interactions by polarizing H 2 . 13 , 18 , 19 2D boron sheets (borophene), which have been recently synthesized, 20 22 have shown a favorable affinity for different metal-decorating atoms, in contrast to graphene, in which clustering of metal atoms can occur. 23 , 24 Using a variety of metal decorations, such as Li, 18 , 19 , 23 Na, 25 Ca, 26 and Ti 27 on different borophene polymorphs, impressive H 2 gravimetric densities have been obtained ranging from 6 to 15 wt %, exceeding the US department of energy (DOE) requirement for onboard storage of 6.5 wt % H 2 .…”
Section: Introductionmentioning
confidence: 99%